INTERVENSI PELATIHAN PENGENALAN DIRI UNTUK MENINGKATKAN SELF ESTEEM PADA REMAJA PENDERITA THALASSAEMIA - Ema Zati Baroroh (Faculty of Psychology Universitas Islam Sultan Agung Semarang, 2022)
The purpose of this study is to provide new insights self-esteem for participants, and to find outcome increasing participant’s self-esteem after participating in the training. This experimental study was conducted for 6 teenagers with thalassemia who were selected based on the specific characteristics proposed. This study used a pure experimental design without control group. Data were collected through interviews and observations before and before treatment. The intervention provided was in the form of personal recognition training. This treatment uses lecture, discussion, brainstorming, and games with light methods. Lasts for 2 times with a duration of 2.5 hours. In general, almost all people who experience development and able to be creative during the material session, and allow participants to have and be able to be more confident. There was a change in the classification of participants, namely DA, DE, L, S, and W. Meanwhile, there was no change in Lu.